Edukasi Pengelolaan Limbah Industri Pabrik Tahu Dan Tempe Anisah Melalui Media Poster Kecamatan Konda, Kabupaten Konawe Selatan Tahun 2025 - Safitri, Wa Ode Mustika Ayu Safitri; Karimuna, Siti Rabbani; Winandari, Alzagita Trisazena; Asis, Zalsabila Reskyta; Israwati; Nurhawa; Kristi, Elsa; Pertiwi, Gadis Andista; Arini, Jenny; Putri, Rizki Amelia Eka; Maftuha, Andi Zakiah Aini; Asnani; Salsabila, Febi Nur; Dzulzahabiyyah, Afifah Azhari; Maulana, Mey Sri; Nugraha, Agung; Juliarto, Dion (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Liquid waste and solid waste are products of tofu and tempeh processing. Solid waste, the end product of the sieving and coagulation process, is then used as flour, tofu biscuits, and animal feed. Liquid waste is the end result of the washing, boiling, pressing, and molding processes. Food businesses in Indonesia are often found in rivers or residential areas, which have a negative impact on the environment, resulting in ugly buildings, and reducing environmental degradation, all of which can contribute to habitat degradation. The tofu, tempeh, and tapioca industries, as well as other food sectors, are among the food industries that produce large environmental impacts. This research was conducted at the Anisah tofu and tempeh factory in Konda District. This research uses a participatory education approach to increase the knowledge of tofu and tempeh factory actors in waste management. The approach method used is the extension and interview method. Based on the results of interviews conducted with the owner of the Anisah tofu and tempeh factory, it is known that there are 3 types of waste produced by the factory, namely liquid waste, solid waste and gas waste. It is expected that the owners of the tofu and tempeh factory industry are advised to start implementing simple and environmentally friendly waste processing methods. Supervision from related agencies also needs to be strengthened so that waste management is carried out consistently and responsibly